Plateros para el Inca: la traducción de documentos en lengua general al castellano en la Audiencia de Lima a fines del siglo XVII - De La Puente Luna, José Carlos (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
A 1693 document sheds light on the translation into Castilian of witness testimonies uttered in the lengua general and recorded in writing a century earlier, as part of the activities of the interpreters-general in Lima’s appellate court (audiencia). The case demonstrates the official admission of written Quechua in judicial procedures as late as the closing decades of the seventeenth century. It reinforces the idea that the use of one or more standard varieties of Quechua by litigants and interpreters made the interpretive work of these translators in plurilingual contexts such as the court’s judicial district possible.

Un documento de 1693 esclarece la labor de traducción de testimonios escritos en lengua general al castellano por parte de los intérpretes de los naturales de la Audiencia de Lima. El caso demuestra el uso oficial de la escritura en quechua como vehículo de la justicia ordinaria y refuerza la idea de que la labor de interpretación en un contexto plurilingüe como el del circuito de la Audiencia fue posible gracias al uso de una o más variantes estándar de quechua, por parte de traductores y litigantes, hasta bien entrado el siglo XVII.
Silversmiths for the Inca: The Translation of Documents from the General Language to Spanish in the Late Seventeenth-Century Lima Audiencia
Keywords: Quechua; Lengua General; Intérpretes; Cultural Legal; Yauyos; https://purl.org/pe-repo/ocde/ford#6.01.01